VALUATION METHODS FOR AGROINDUSTRIAL COMPANIES - Leal, Rodrigo Bonini; Lopes Santos, David Ferreira [UNESP] (Editora Univ Estado Bahia, 2017)
The aim of this study was to assessment valuation method for to value agribusiness companies. To achieve this goal was made a comparative empirical study of two representative companies in the sector, Sao Martinho Group and JBS, considering financial data for the last three years. The companies were valued according to three methods of valuation: the Valuation Multiples, the Discounted Cash Flow (DCF) and the Real Option Theory (ROT). The results show the Discounted Cash Flow being more efficient in the analysis of the two companies when viewed together, which did not occur when taken separately, where multiple Price/Book Value showed the best performance for the Sao Martinho Group and the Discounted Cash Flow in the JBS case. The TOR was the approach that most attributed value to organizations because of the flexibility of using the abandon option.
Keywords: Agribusiness; Discounted Cash Flow; Investment; Multiples; Real Option Theory